Smart solutions for overcoming anemia emergencies in young girls using Tricky Card Games Education Methods and Smartphone Monitoring Alert Systems - Ningtyias, Farida Wahyu; Aryatika, Karera; Irmayanti, Selvi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: The government has made efforts in the prevention and management of anemia through the distribution of Iron Supplementation Tablets (IST) in schools. One of the problems facing by the government and schools is lack of periodic measurement of hemoglobin levels. Furthermore, there was no socialization source of iron comes from foods by schools.Materials and Methods : The aimed of this study is to increase adolescent knowledge about foods source of iron and also to monev government IST among adolescent. This research is a quasy experimental with a one group pretest-posttest design. Experimental study conducted at MTSN X Jember with a total of 30 female adolescent respondents who fused into one intervention group. Supplementation of IST (1 tablet per week) was provided for 8 weeks (November-December 2021). Improving knowledge among adolescent was measured using Tricky Card Games and pre-posttest questionnaires. Hemoglobin levels were measured before and after the intervention, and monitoring and education were conducted as reminders for taking the tablets through the Monev IST application and a WhatsApp Group. Monitoring and evaluation of adolescent’s adherence for IST consumption using Monev Tablet Tambah Darah application which can download by each adolescent smartphone and also connected with supervisor.Results: The results showed an increase in hemoglobin levels after the treatment, with pre-treatment levels ranging from 9.1 g/dL to 16 g/dL, and an average of 13.53 g/dL, while post-treatment levels ranged from 8.1 g/dL to 17.2 g/dL, with an average of 13.67 g/dL. There was a significant increase in knowledge of foods source iron among adolescent (p < 0.05). However, there was no significant difference in hemoglobin levels (p > 0.05) or consumption patterns (p > 0.05) after the intervention through the tricky card game.Conclusion: Giving IST regularly can increase Hb levels supported by improving knowledge and consumption patterns can be a solution to handling anemia in adolescent girls.Keywords : Anemia; counseling; level of knowledge; consumption patterns; young women